2023
DOI: 10.1007/s10198-023-01593-8
|View full text |Cite
|
Sign up to set email alerts
|

A cost-of-illness study of Behçet syndrome in Italy

Abstract: Objective This study aims at evaluating the cost-of-illness (COI) of patients diagnosed with Behcet’s syndrome (BS) in Italy, trying to depict the impact of different costs’ components to the overall economic burden and analysing the variability of costs according to years since diagnosis and age at first symptoms. Methods With a cross-sectional evaluation, we surveyed a large sample of BS patients in Italy assessing several dimensions related to BS, also … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 22 publications
(27 reference statements)
0
1
0
Order By: Relevance
“…The global prevalence 2017 reached 14.6 per 100,000, with even higher prevalence rates along the Silk Route, like Turkey, with 420 per 100,000 [9,2]. Moreover, it is reported that every patient with Behçet's disease has a health cost of roughly 21,600€ per year, which may lead to financial problems [10]. Severe morbidities are associated with Behçet's due to the wide range of affected organs and systems, although most of the lasting complications are focused on the ocular and mucocutaneous regions.…”
Section: Introductionmentioning
confidence: 99%
“…The global prevalence 2017 reached 14.6 per 100,000, with even higher prevalence rates along the Silk Route, like Turkey, with 420 per 100,000 [9,2]. Moreover, it is reported that every patient with Behçet's disease has a health cost of roughly 21,600€ per year, which may lead to financial problems [10]. Severe morbidities are associated with Behçet's due to the wide range of affected organs and systems, although most of the lasting complications are focused on the ocular and mucocutaneous regions.…”
Section: Introductionmentioning
confidence: 99%